2020
DOI: 10.1111/add.15344
|View full text |Cite
|
Sign up to set email alerts
|

Craving mediates the association between momentary pain and illicit opioid use during treatment for opioid‐use disorder: an ecological momentary assessment study

Abstract: Aim To assess the role of momentary pain on opioid craving and illicit opioid use among individuals receiving opioid agonist treatment. Design Observational study using ecological momentary assessment. Setting The National Institute of Drug Abuse Intramural Research Program in the United States. Participants Fifty-six adults who qualified for opioid agonist treatment. Measurements Participants completed randomly prompted assessments of pain severity, stress, negative mood, opioid craving and illicit opioid use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…However, sleep disturbance remains a major issue in patients maintained on both methadone and buprenorphine (Brady, 2001;Dunn et al, 2018;Finan et al, 2020) and drug craving is associated with sleep disturbance during the early stages of opioid abstinence (Fathi et al, 2020). Drug use and craving are also associated with depressive symptoms, negative affect, and anhedonia in methadone-maintained patients (Epstein et al, 2009;Huhn et al, 2019;Huhn, Brooner, et al, 2020;Mun et al, 2020). Given that sleep disturbance is a symptom of depressive disorders (Tsuno et al, 2005), it is likely that there is a link among sleep, psychiatric symptoms, and treatment outcomes in this population.…”
Section: Sleep Stress and Emotional Processes In Persons Withmentioning
confidence: 99%
See 2 more Smart Citations
“…However, sleep disturbance remains a major issue in patients maintained on both methadone and buprenorphine (Brady, 2001;Dunn et al, 2018;Finan et al, 2020) and drug craving is associated with sleep disturbance during the early stages of opioid abstinence (Fathi et al, 2020). Drug use and craving are also associated with depressive symptoms, negative affect, and anhedonia in methadone-maintained patients (Epstein et al, 2009;Huhn et al, 2019;Huhn, Brooner, et al, 2020;Mun et al, 2020). Given that sleep disturbance is a symptom of depressive disorders (Tsuno et al, 2005), it is likely that there is a link among sleep, psychiatric symptoms, and treatment outcomes in this population.…”
Section: Sleep Stress and Emotional Processes In Persons Withmentioning
confidence: 99%
“…Studies using ecological momentary assessments have also demonstrated that momentary levels of stress and related psychophysiological states such as low positive affect, high negative affect, and pain are associated with opioid craving (Huhn et al, 2016; Mun et al, 2020) and that low positive affect, or anhedonia, partially mediates the relationship between sleep quality and opioid craving in postwithdrawal OUD patients (Lydon-Staley et al, 2017). These studies have focused on within-day and/or point prevalence associations of psychological states and drug use behavior, for example, whether stress is associated with craving at the moment .…”
Section: Sleep Stress and Emotional Processes In Persons With Opioid ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, EMA research with adults in MOUD treatment demonstrated a stronger relationship between craving and drug use events than between stress and drug use events (41). EMAassessed momentary pain has been shown to be indirectly associated with illicit opioid use via momentary opioid craving (42). Further, MOUD treatment dropout has been shown to be more likely among individuals who report more "hassles", higher levels of cocaine craving, lower levels of positive mood, a recent history of emotional abuse, and a recent history of being bothered frequently by psychological problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, artificial stimuli and strict laboratory settings far from real-life contexts did not fully reveal the ephemeral and fluctuant nature of craving dynamics ( Enkema, Hallgren, Bowen, Lee, & Larimer, 2021 ). Fortunately, mobile technologies, such as ecological momentary assessment (EMA; Stone & Shiffman, 1994 ), have permitted real-time data collection in natural contexts and therefore offer a solution to numerous methodological barriers to emotion and addiction research ( Mun et al., 2021 ). The feasibility and validity of the EMA have been repeatedly established in individuals with different addiction syndromes (see review from Serre, Fatseas, Swendsen, & Auriacombe, 2015 ).…”
mentioning
confidence: 99%